An Analysis of Students' Ability and Difficulties to Use Auxiliary Verbs in Writing Descriptive Text at First Grade Vacational High School Parulian 3 Medan - Simatupang, Ayu Lestari; Lestari, Febrika Dwi; Simarmata, Rina Octavia (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
This study seeks to characterize the proficiency and identify the challenges encountered by tenth-grade students at SMK 3 Parulian Medan in employing auxiliary verbs within the context of descriptive text writing. Employing a qualitative descriptive research design, this study aimed to describe the competence and pinpoint the obstacles faced by tenth-grade students at SMK 3 Parulian Medan in applying auxiliary verbs within descriptive text writing. Data were gathered through an analysis of the written works produced by 20 students following a task to compose descriptive texts. The data collection technique involved providing clarification regarding the nature of descriptive texts and offering illustrative examples of descriptive texts centered on the topic of describing a place. The findings indicated that, in general, tenth-grade students at SMK 3 Parulian Medan exhibited a satisfactory proficiency in writing descriptive texts, achieving an average score of 81.65. An analysis of their auxiliary verb usage revealed a total of 122 words, comprising 42 instances of "to have," 2 instances of "to do," and 15 instances of modal auxiliary verbs. However, a more in-depth analysis unveiled persistent difficulties in students' application of auxiliary verbs. This is attributed to a perceived lack of attention to the relevant learning materials during classroom instruction.